2023
DOI: 10.2196/43203
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Key Factors Influencing Nursing Students’ Cognitive Load and Willingness to Serve Older Adults: Cross-sectional Descriptive Correlational Study

Abstract: Background Virtual learning environments (VLEs) use a virtual environment to support learning activities. VLEs are commonly used to overcome the temporal and spatial restrictions of learning activities held in conventional face-to-face classrooms. In VLEs, students can participate in learning activities using the internet, and teachers can provide assistive learning tools during the process. Objective The purpose of this study was to investigate the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Advances in CLT have set the trends for future developments in different learning environments such as workplace-based learning, simulation, and games [15]. Most studies used the CLT principles in instructional design in simulation, virtual reality, and game settings in nursing education [1,[16][17][18]. Yiin et al, (2023) indicated the multi-media interactive learning materials and an active learning mechanism reduced nursing students' intrinsic and extrinsic cognitive load and encouraged the students to learn [19].…”
Section: Clt In Health Professions Educationmentioning
confidence: 99%
“…Advances in CLT have set the trends for future developments in different learning environments such as workplace-based learning, simulation, and games [15]. Most studies used the CLT principles in instructional design in simulation, virtual reality, and game settings in nursing education [1,[16][17][18]. Yiin et al, (2023) indicated the multi-media interactive learning materials and an active learning mechanism reduced nursing students' intrinsic and extrinsic cognitive load and encouraged the students to learn [19].…”
Section: Clt In Health Professions Educationmentioning
confidence: 99%
“…The significance of research on cognitive and non-cognitive factors influencing academic performance among nursing students is essential (Hollinger-Smith et al, 2023). Understanding the role of cognitive factors will enable nursing educators to focus on cultivating them in nursing students (Hsieh, Wang, & Huang, 2023). Examining non-cognitive factors will inform nurse educators on how to address them to foster academic success among nursing students (Ang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%